Best Practices in Real Estate Cross-border Transactions - Szulc, Piotr (Studia Prawa Publicznego, 2020)
The article presents reflections on the best practices in real estate cross border transactions.Transactions on real estate markets have several aspects that make them highly complex, mostly due to their individual nature – each property is unique in terms of its location, structure and history. Cross-border transactions on the real estate market are becoming increasingly popular as the world becomes more globalized. The growing volume of this type of transaction presents a challenge for the modern real estate lawyer. It is impossible to create an exhaustive guide setting out all the hazards occurring in such transactions. This article addresses this difficult challenge by indicating the most important of them. It is essential and extremely helpful to enter into cooperation with a local counsel who will help us to explain the local specificity and who will take the legal differences into account. In addition, other helpful tools, such as a legal due diligence report or a title insurance Policy, should be carefully considered. One cannot forget about the importance of the local culture and customs, which may prove decisive at the crucial moment of the transaction. Finally, to be effective in working with cross-border clients, lawyers must have a good understanding of how people think and make decisions, and must possess good people skills. Respect for local customs and traditions, as well as understanding the local legal system while securing clients’ interests, is the key to a successful transaction.